2014
DOI: 10.3389/fnhum.2014.00763
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activity associated with the detection of temporal gaps in tones: a magnetoencephalography study

Abstract: We used magnetoencephalogram (MEG) in two experiments to investigate spatio-temporal profiles of brain responses to gaps in tones. Stimuli consisted of leading and trailing markers with gaps between the two markers of 0, 30, or 80 ms. Leading and trailing markers were 300 ms pure tones at 800 or 3200 Hz.Two conditions were examined: the within-frequency (WF) condition in which the leading and trailing markers had identical frequencies, and the between-frequency (BF) condition in which they had different freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…We first monitored activity in the frontal and parietal regions, as well as in the AC. Estimation was performed according to the methods used in our previous works 41 , 42 . To avoid double dipping 43 , we marked iROIs on the AC, IFG, and TPJ of both hemispheres by referencing previous studies and using the anatomical information provided by FreeSurfer software (l(r)h.aparc.annot based on Desikan-Killiany Atlas 44 ).…”
Section: Methodsmentioning
confidence: 99%
“…We first monitored activity in the frontal and parietal regions, as well as in the AC. Estimation was performed according to the methods used in our previous works 41 , 42 . To avoid double dipping 43 , we marked iROIs on the AC, IFG, and TPJ of both hemispheres by referencing previous studies and using the anatomical information provided by FreeSurfer software (l(r)h.aparc.annot based on Desikan-Killiany Atlas 44 ).…”
Section: Methodsmentioning
confidence: 99%
“…As far as we know, Grose et al [6] was the only study that measured ABRs in the context of across-channel gap detection, although they used a two-tone complex marker which is not typical in gap detection research. In the present study, we used narrowband noise markers of center frequencies similar to the frequencies of pure tone markers used in studies of the first author's lab [8].…”
Section: Introductionmentioning
confidence: 99%
“…Second, ABR data should be useful for identifying, along the auditory pathway, the site responsible for differences between within-channel and across-channel gap detection. Neurophysiological studies of gap detection, particularly with human participants, have indicated that neural activities differ between the two types of gap detection at the auditory cortex or higher brain regions [4,8,9]. However, it is conceivable that differences may exist at lower stages of the auditory pathway.…”
Section: Introductionmentioning
confidence: 99%
“…There are also studies focusing on the auditory system, including the work of Nakajima et al that investigates the foundations of time perception using a time illusion based on an overestimation of a second time interval preceded by a first time interval or time-shrinking effect (Nakajima et al, 2014 ). Mitsudo et al present recorded magnetoencephalogram signals in tasks that require to judge temporal gaps in tones and have discussed their implications in the organization of the auditory cortex (Mitsudo et al, 2014 ). Within the same time perception paradigm, Mioni et al show a detailed review on temporal dysfunctions in traumatic brain injury patients (Mioni et al, 2014 ).…”
mentioning
confidence: 99%